2020
DOI: 10.3390/f11101096
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of the Cocoa Agroforests of the Bengamisa-Yangambi Forest Landscape in the Democratic Republic of the Congo (DRC)

Abstract: Cocoa agroforestry has evolved into an accepted natural resource conservation strategy in the tropics. It is regularly proposed as one of the main uses for REDD+ projects (Reducing Emissions from Deforestation and forest Degradation and the role of conservation, sustainable management of forests, and enhancement of forest carbon stocks in developing countries) in the Democratic Republic of the Congo. However, few studies have characterized the cocoa agroforestry systems in this country. Hence, this research pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
4
0
3
Order By: Relevance
“…The tree species found in respondents’ fields are of some interest to farmers (Batsi et al , 2020). Petersianthus macrocarpus and Persea americana are the two preferred species; the former is home to edible caterpillars and the latter provides edible fruits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tree species found in respondents’ fields are of some interest to farmers (Batsi et al , 2020). Petersianthus macrocarpus and Persea americana are the two preferred species; the former is home to edible caterpillars and the latter provides edible fruits.…”
Section: Discussionmentioning
confidence: 99%
“…However, these practices are adopted by a very small proportion of respondents and are not yet being promoted. Note that agroforestry is already practiced by famers in some corners of the Yangambi landscape (Batsi et al , 2020) but only by a few. Onyeneke et al (2017) reported that farmers have already adopted CSA practices in southeast Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…La richesse spécifique est importante dans les forêts secondaires et se rapproche de celle des forêts matures (Chazdon et al, 2009). La richesse spécifique dans les plantations des cacaoyers à Yangambi est supérieure à celle rapportée par Batsi et al (2020) dans le paysage Bengamisa-Yangambi. Cette différence serait liée au mode d'installation des plantations, celles de Yangambi étant installées sur les terres forestières dégradées avec plusieurs espèces d'arbres forestiers laissées en place, alors que les cacaoyères du paysage Bengamisa-Yangambi ont été plantées sous des palmeraies (Batsi et al, 2020).…”
Section: Structure Diversité Et Composition Arboréeunclassified
“…L'agroforesterie à base de cacaoyers est une stratégie fréquemment proposée dans des projets REDD+ (Réduction des émissions dues à la déforestation et à la dégradation des forêts) de la RDC, pour éviter la déforestation, tout en améliorant les conditions de vie des ménages paysans. Dans cette étude, nous avons pu démontrer que les cacaoyères présentent des niveaux de biomasse et de diversité élevés par rapport aux autres systèmes agroforestiers, mais un choix judicieux des zones d'installation des plantations est nécessaire, pour éviter que ces dernières remplacent les forêts matures et deviennent une source de déforestation, comme déjà signalé dans d'autres zones de la RDC (De Beule et al, 2014 ;Batsi et al, 2020).…”
Section: Trajectoire De Conversion (Dégradation Et Déforestation) Et ...unclassified
“…Globalmente, este cultivo es el sustento de 5 millones de pequeños productores, además de generar empleo para 40-50 millones de personas (Voora et al, 2019;Cámara Café Cacao, 2021). Asimismo, bajo un sistema agroforestal, el cacaotal puede albergar diferentes especies de plantas (Ordoñez y Rangel, 2020;Batsi et al, 2020) e insectos (Indriati et al, 2019) por lo tanto tiene una gran importancia en la conservación de la biodiversidad; además de mitigar los efectos del cambio climático mediante la captura de carbono (Zavala et al, 2018;Asigbaase et al, 2021).…”
Section: Introductionunclassified